Surgical stabilization of acetabular injuries: approaches and methods. Issue 2 (April 2022) - Rawal, Jaikirty; Arshad, Homa; Bates, Peter
Abstract: Surgical approaches to the acetabulum are key to providing adequate exposure and reduction of fracture fragments thereby restoring articular congruity. Here, we discuss both the anterior and the posterior approaches in common practice but also the techniques available to help achieve reduction.